Analysis of the mechanical stability and surface detachment of mature Streptococcus mutans biofilms by applying a range of external shear forces - Hwang, Geelsu; Klein, Marlise I. [UNESP]; Koo, Hyun (Taylor & Francis, 2014)
Well-established biofilms formed by Streptococcus mutans via exopolysaccharide matrix synthesis are firmly attached to tooth surfaces. Enhanced understanding of the physical properties of mature biofilms may lead to improved approaches to detaching or disassembling these highly organized and adhesive structures. Here, the mechanical stability of S. mutans biofilms was investigated by determining their ability to withstand measured applications of shear stress using a custom-built device. The data show that the initial biofilm bulk (~ 50% biomass) was removed after exposure to 0.184 and 0.449 N m−2 for 67 and 115 h old biofilms. However, removal of the remaining biofilm close to the surface was significantly reduced (vs initial bulk removal) even when shear forces were increased 10-fold. Treatment of biofilms with exopolysaccharide-digesting dextranase substantially compromised their mechanical stability and rigidity, resulting in bulk removal at a shear stress as low as 0.027 N m−2 and > a two-fold reduction in the storage modulus (G′). The data reveal how incremental increases in shear stress cause distinctive patterns of biofilm detachment, while demonstrating that the exopolysaccharide matrix modulates the resistance of biofilms to mechanical clearance.
Keywords: dextranase; exopolysaccharide matrix; mechanical stability; rheometry; S. mutans biofilm; shear stress